Analytical methods for determination of sugar content in fruit juices: from classical methods to modern analytical techniques - Oliver Majstorov; Tanja Petreska Ivanovska; Zoran Zhivikj; Lidija Petrushevska-Tozi; Rumenka Petkovska; Liljana Anastasova (Makedonsko Farmacevtski Bilten)
The determination and quantification of sugars in fruit juices is especially important for quality control. In this article, the analytical methods for determination of sugars in fruit juices are presented and discussed. Available methods range from classical methods based on Fehling’s and Luft-Shorl’s methods, refractometric or enzymatic to liquid chromatography with different types of detectors. Although chromatography has been extensively used as a very accurate and sensitive technique, the sample preparation is time consuming and requires solvent extraction. Spectroscopic techniques (FTIR-ATR, MIR, Raman) have been recognized as potential and valuable alternative to chromatographic methods, since they are easy, simple and in many cases non-destructive. These methods that are fast, easy to use and non-destructive are in line with current analytical trends however they must be properly calibrated and validated.